Language use, language attitude, and identity: Perceptions of high school students attending an international school in Jakarta - Katharina Endriati Sukamto; Maria Fe Suganob Nicolau; K.R. Vinitha Rani; Sugiyanta Sugiyanta (Universitas Syiah Kuala, 2021)
This study explores the perceptions of high school students who attend an international school in Jakarta towards language use, language attitude, and identity. One hundred sixty-five students aged between 15-18 years old participated in this study. They were divided into three categories based on their nationalities, namely (1) Indonesian students who were born and raised in Indonesia, (2) Indonesian students who were born and raised outside Indonesia, and (3) non-Indonesian students (expatriates) who were studying in Indonesia. The data were collected using a survey and in-depth interviews. The findings reveal that the majority of the students in the first and second categories were more comfortable with both oral and written English rather than their first language. However, for the expatriates in the third group, they could express themselves better when they used their first language. Generally, their attitude towards their home language was quite positive. The need to speak their first language (e.g., Korean, Hindi) was a gateway to connect with friends and relatives who did not speak English. As for the students’ identity, this study reveals that although the students were more fluent in English, they felt that they were strongly connected to their country of birth. This study draws out the pedagogical implication that the use of English as a medium of instruction can be quite critical, especially for Indonesian students, as it may have an impact on the loss of their home language.